2015
DOI: 10.1109/jphot.2014.2387253
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvements for AlGaN-Based Deep Ultraviolet Light-Emitting Diodes With the p-Type and Thickened Last Quantum Barrier

Abstract: In order to improve the performance of AlGaN-based deep ultraviolet lightemitting diodes (UV LEDs), the optical and physical properties of AlGaN-based deep UV LEDs with a p-type and thickened last quantum barrier (LQB) are studied numerically. The output power-current performance curves, internal quantum efficiency, electroluminescence intensity, energy band diagrams, distributions of carrier concentrations, and the radiative recombination rates in the active region are investigated by Advance Physical Model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“… However, the optical output power of current UVC LEDs drops significantly as the light emission wavelength gets shorter. Those LEDs suffer from poor hole injection efficiency in high‐Al‐content p‐type AlGaN, low internal quantum efficiency (IQE) caused by large‐lattice‐mismatch heteroepitaxy, and strong quantum‐confined Stark effect (QCSE), as well as the absorption by the nontransparent GaN contact layers …”
mentioning
confidence: 99%
“… However, the optical output power of current UVC LEDs drops significantly as the light emission wavelength gets shorter. Those LEDs suffer from poor hole injection efficiency in high‐Al‐content p‐type AlGaN, low internal quantum efficiency (IQE) caused by large‐lattice‐mismatch heteroepitaxy, and strong quantum‐confined Stark effect (QCSE), as well as the absorption by the nontransparent GaN contact layers …”
mentioning
confidence: 99%
“…The internal quantum efficiency (IQE) can thus be largely improved for the acquired structures, which were grown by either metal‐organic vapor phase epitaxy (MOVPE) or molecular beam epitaxy (MBE) . However, the output power and emission efficiency of the mid‐ or deep‐UV light sources are still much poorer than those of blue light emitting diodes (LEDs) because they suffer from several inherent issues, in particular the transverse magnetic (TM, E // c ) polarized emission involvement, poor crystalline quality of the AlGaN active region, difficulty in p‐type doping for high‐Al‐content AlGaN layers, and inevitable light absorption in the commonly used p‐type GaN injection layers …”
mentioning
confidence: 99%
“…Many studies have reported strategies of defect reduction via substrate or template, [18][19][20] methods of high carrier connement, and hole injection. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Low light extraction efficiency (LEE) is another challenge in achieving high efficiency for DUV LEDs. The LEE of the DUV LEDs has been improved by utilizing the ip-chip design, 36,37 a patterned sapphire substrate, 20,38 a patterned p-type layer, 39 and the nanowire structure.…”
Section: Introductionmentioning
confidence: 99%